2013
DOI: 10.2334/josnusd.55.225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bioactive glass and platelet-rich plasma for bone healing in rabbit calvarial defects

Abstract: Bone regeneration is an important objective in clinical dental practice and has been used for different applications. The aim of this study was to evaluate the effectiveness of platelet-rich plasma (PRP) and bioactive glass (BG) for bone healing of surgical calvarial defects in rabbits. Two 8-mm defects were prepared in the parietal bones of ten animals, and the animals were randomly assigned to two groups. In each group, two subgroups were created with five defects each: BC - blood clot, BG, PRP and PRP + BG.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
4
0
3
Order By: Relevance
“…Although there was success in these studies, these methods are not commonly used in clinical practice. [1,2,[4][5][6] It was realized that bone metabolism is regulated through various chemical and metabolic pathways, and that certain peptides (growth factors) are released from platelets, macrophages, and fibroblasts during the union of fractures. These proteins are known to organize delicate processes such as proliferation, differentiation, migration, and resorption in the healing of fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was success in these studies, these methods are not commonly used in clinical practice. [1,2,[4][5][6] It was realized that bone metabolism is regulated through various chemical and metabolic pathways, and that certain peptides (growth factors) are released from platelets, macrophages, and fibroblasts during the union of fractures. These proteins are known to organize delicate processes such as proliferation, differentiation, migration, and resorption in the healing of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoconductive agents such as ceramics, polymers, trabecular metals, and bioactive glass have been employed to provide mechanical support for vascular and bone ingrowth. [4,5] Osteoinductive growth factors, autogenic bone…”
mentioning
confidence: 99%
“…While some studies in cranial and mandibular defects showed that the addition of PRP to xenografts, alloplastic materials or scaffolds improved bone formation compared to the use of the grafts/scaffolds alone (Aghaloo, Moy & Freymiller, ; Chen, Lu, Liu, Tang & Zhang, ; El Backly, Zaky, Canciani, Saad & Eweida, ; Hirota, Matsui, Mizuki, Kishi & Watanuki, ; Kim, Kim, Kim, Lim & Kim, ; Li, Chen, Wei, Hao & Wang, ; Penteado, Colombo, Penteado, Assis & Gurgel, ; Schlegel et al., ), other studies did not confirm these findings (DeNicolo, Guyton, Cuenin, Hokett & Sharawy, ; Faratzis, Leventis, Chrysomali, Khaldi & Eleftheriadis, ; Plachokova, Dolder, Stoelinga & Jansen, ; Rocha, Ramos, Batista, Zanetta‐Barbosa & Ferro, ; Wiltfang et al., ) or showed that the use of MSCs in conjunction with bone substitutes could enhance bone regeneration more than PRP (Khojasteh, Eslaminejad & Nazarian, ). It was also shown that adding PRP to GBR (Kazakos, Lyras, Thomaidis, Agrogiannis & Botaitis, ) or to BMP (Ferraz, Schellini, Schellini, Pellizon & Hirai, ) did not accelerate the bone formation process.…”
Section: Resultsmentioning
confidence: 99%
“…However, single (alone) or complementary (with other biomaterial) effect of PRP still needs more clarification especially through in vivo studies. For assurance, there have been multiple trials evaluating the effect of PRP merged with BG (not the type used here) on human and animals (only with oral and maxillofacial defects), nonetheless, this combination remains questionable (Demir et al, 2007;Trindade-Suedam et al, 2010;Penteado et al, 2013). Therefore, the main concept of the study outlined here was to compare the regenerative potentiality of PRP, 45S5BG or BG/PRP in treatment of metaphyseal tibia defects in a rabbit model.…”
Section: Introductionmentioning
confidence: 99%